2011
DOI: 10.1055/s-0031-1296655
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antihyperlipidemic Activity of Some Novel Condensed 2-Chloroalkyl-4-chloro/hydroxy-5,6-disubstituted Pyrimidines

Abstract: Synthesis and antihyperlipidemic activity of a series of novel condensed 2-chloroalkyl-4-chloro/hydroxy-5,6-di-substituted pyrimidines are described. The design of these compounds is based on the earlier QSAR study on the antihyperlipidemic 2-substituted methylthienopyrimidin-4-ones. The newly synthesized condensed 4-chloro-2-chloroalkylpyrimidines (IIIa-n) have exhibited much superior antihyperlipidemic activity, compared to their earlier reported 4-hydroxy analogs. Notably, in this series, five compounds, II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In continuation of our ongoing work on condensed thienopyrimidines and quinazolines [30,31], we herein report the fused heterocyclic derivatives of thienopyrimidine and quinazoline as divalent and ring equivalent isosteres of Rutaecarpine. Hence a series of novel heterocyclic compounds belonging to thienopyrimidine fused with quinazoline, substituted thiophene, pyridothiophene and quinazoline fused with substituted thiophene, pyridothiophene, quinazoline were synthesized using ionic liquid and DMSO.…”
Section: Introductionmentioning
confidence: 97%
“…In continuation of our ongoing work on condensed thienopyrimidines and quinazolines [30,31], we herein report the fused heterocyclic derivatives of thienopyrimidine and quinazoline as divalent and ring equivalent isosteres of Rutaecarpine. Hence a series of novel heterocyclic compounds belonging to thienopyrimidine fused with quinazoline, substituted thiophene, pyridothiophene and quinazoline fused with substituted thiophene, pyridothiophene, quinazoline were synthesized using ionic liquid and DMSO.…”
Section: Introductionmentioning
confidence: 97%
“…With reference to QSAR methodology for carbonic anhydrase inhibitors, topoisomerase inhibitors, anti‐hyperlipidemic activity, and TMP kinase inhibitors, we here report in detail a QSAR study using “QSARINS” for carbonic anhydrase IX inhibitors. In the present study, the dataset series of triazole benzene sulphonamides derivatives as inhibitors of carbonic anhydrase IX were taken from PK Sharma et al The dataset was subjected to the software for predicting the role of substituent on biological activity by generating efficient models, which are capable of estimating bioactivities of newly designed compounds with extensive parameters available within the software.…”
Section: Introductionmentioning
confidence: 99%
“…Drugs used as reference standards in these studies were gemfibrozil, clofibrate, riboflavin tetrabutyrate, ezetimibe. Further, the acute and chronic toxicity studies of this compound indicated it to be considerably safe with high LD 50 values (Shishoo et al 1990, 1981, 1996; Jain et al 2011; Arya 1985; Kathiravan et al 2007).
Figure 1 LM-1554- The title compound.
…”
Section: Introductionmentioning
confidence: 99%
“…QSAR studies undertaken on its analogs revealed the electronic parameter to be positively contributing to the antihyperlipidemic activity of these compounds. Electron withdrawing groups (EWG) attached at the 2-methyl substituent of these compounds, enhanced the activity (Shishoo et al 1996; Kathiravan et al 2007). All these interesting observations aroused our interest to probe into the pharmacodynamics of this compound.…”
Section: Introductionmentioning
confidence: 99%